The chromokinesin Klp3a and microtubules facilitate acentric chromosome segregation. - Karg, T.; Elting, M.W.; Vicars, H.; Dumont, S.; Sullivan, W. (Journal of Cell Biology, 2017)
Although poleward segregation of acentric chromosomes is well documented, the underlying mechanisms remain poorly understood. Here, we demonstrate that microtubules play a key role in poleward movement of acentric chromosome fragments generated in Drosophila melanogaster neuroblasts. Acentrics segregate with either telomeres leading or lagging in equal frequency and are preferentially associated with peripheral bundled microtubules. In addition, laser ablation studies demonstrate that segregating acentrics are mechanically associated with microtubules. Finally, we show that successful acentric segregation requires the chromokinesin Klp3a. Reduced Klp3a function results in disorganized interpolar microtubules and shortened spindles. Normally, acentric poleward segregation occurs at the periphery of the spindle in association with interpolar microtubules. In klp3a mutants, acentrics fail to localize and segregate along the peripheral interpolar microtubules and are abnormally positioned in the spindle interior. These studies demonstrate an unsuspected role for interpolar microtubules in driving acentric segregation.